2006
DOI: 10.1007/s10563-006-9001-1
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and desorption of small molecules for the characterization of solid acids

Abstract: The relative acid strength and acid amount of solid acids has been determined from the adsorption and desorption of small molecules, such as argon. The order of activation energy for desorption of Ar from a solid acid, determined using temperatureprogrammed desorption (TPD), is sulfated zirconia > Cs 2.5 H 0.5 PW 12 O 40 > proton-type zeolites > silica-alumina. The adsorption isotherms were analyzed using Langmuir and Henry equations. The Henry-type adsorption isotherms were also analyzed using the theory of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…For the answer to this question, we tried the use of Ar as a probe atom for the evaluation of the acid strength of solid superacids, and it was shown that the acid strength of the present catalysts is higher than that of any zeolites, determined by new methods of temperature-programmed desorption of Ar and of the heat of adsorption of Ar. [108][109][110][111][112] The studies of organic synthesis have been limited to a few of the catalytic materials, mainly sulfated zirconia. All the materials prepared show their own catalytic properties; it is advisable that other superacidic substances should be extensively studied.…”
Section: Discussionmentioning
confidence: 99%
“…For the answer to this question, we tried the use of Ar as a probe atom for the evaluation of the acid strength of solid superacids, and it was shown that the acid strength of the present catalysts is higher than that of any zeolites, determined by new methods of temperature-programmed desorption of Ar and of the heat of adsorption of Ar. [108][109][110][111][112] The studies of organic synthesis have been limited to a few of the catalytic materials, mainly sulfated zirconia. All the materials prepared show their own catalytic properties; it is advisable that other superacidic substances should be extensively studied.…”
Section: Discussionmentioning
confidence: 99%
“…Among the metal oxides, tin(IV) oxide exhibits the largest increase in acidity resulting from the introduction of sulfate anions. The acid strength of sulfated tin(IV) oxide was determined using the Hammett indicator method [14], temperature-programmed desorption of pyridine [15], and measurement of the heat of Ar adsorption [16,17]. In the present study, SnO 2 was mixed with TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In 1979, Hino et al [1] indicated, for the first time, that the acid strength of the SO 4 2− /ZrO 2 catalyst is estimated to be H 0 (Hammett indicator) ≥ -14.52, one of the strongest solid superacids. Sulfated zirconia (SO 4 2 /ZrO 2 ) is a typical solid superacid and exhibits a high catalytic activity for the skeletal isomerization of saturated hydrocarbons and other reactions [2][3][4][5][6]. Sulfated tin oxide (SO 4 2− /SnO 2 ) was later reported by Matsuhashi et al [4] to be one of the candidates with the strongest acidity, acid strength of which is almost equal to that of SO 4 2− / ZrO 2 at least [7][8][9].…”
Section: Introductionmentioning
confidence: 99%